Overview of the Complex Figure Test and Its Clinical Application in Neuropsychiatric Disorders, Including Copying and Recall - Zhang, Xiaonan; Lv, Liangliang; Min, Guowen; Wang, Qiuyan; Zhao, Yarong; Li, Yang (Frontiers in Neurology, 2021)
The Rey-Osterrieth Complex Figure test (ROCF) is a commonly used neuropsychological assessment tool. It is widely used to assess neuropsychiatric disorders' visuo-constructional ability and visual memory, including copying and recall tests. By drawing the complex figure, the patient's functional decline in multiple cognitive dimensions can be assessed, including attention and concentration, fine-motor coordination, visuospatial perception, nonverbal memory, planning and organization, and spatial orientation. This review first describes the different versions and scoring methods of ROCF. It then reviews the application of ROCF in the assessment of visuo-constructional ability in patients with dementia, other brain diseases, and psychiatric disorders. Finally, based on the scoring method of the digital system, future research hopes to develop a new digital ROCF scoring method combined with machine learning algorithms to standardize clinical practice and explore the characteristic neuropsychological structure information of different disorders.